2006
DOI: 10.1109/iccd.2006.4380859
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Evaluation of On-Chip Network Architectures

Abstract: Abstract-Driven by the need for higher bandwidth and complexity reduction, off-chip interconnect has evolved from proprietary busses to networked architectures. A similar evolution is occurring in on-chip interconnect. This paper presents the design, implementation and evaluation of one such on-chip network, the TRIPS OCN. The OCN is a wormhole routed, 4x10, 2D mesh network with four virtual channels. It provides a high bandwidth, low latency interconnect between the TRIPS processors, L2 cache banks and I/O un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
82
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(83 citation statements)
references
References 13 publications
1
82
0
Order By: Relevance
“…Our earlier work examining the OCN [22] showed that real benchmark generated traffic in on-chip networks would not be modeled well by traditional synthetic loads. We perform a similar analysis for the OPN using network traces generated from tsim-cyc and characterize the network workload.…”
Section: Opn Traffic Trace Analysismentioning
confidence: 99%
“…Our earlier work examining the OCN [22] showed that real benchmark generated traffic in on-chip networks would not be modeled well by traditional synthetic loads. We perform a similar analysis for the OPN using network traces generated from tsim-cyc and characterize the network workload.…”
Section: Opn Traffic Trace Analysismentioning
confidence: 99%
“…The completely bufferless designs either drop [19,16] or misroute (deflect) [38] flits when contention occurs. Eliminating buffers is desirable: buffers draw a significant fraction of NoC power [21] and area [17], and can increase router latency. Moscibroda and Mutlu [38] report 40% network energy reduction with minimal performance impact at low-to-medium network load.…”
Section: Introductionmentioning
confidence: 99%
“…In order to fully exploit the increasing number of cores and get enough parallelism for applications, virtualization for multicore chips is becoming necessary [8], [10], [11], [12]. The virtualized NoC solution provides several advantages such as increasing resource utilization, reducing power consumption and increasing the yield of chips [11].…”
Section: Introductionmentioning
confidence: 99%
“…The Regular topology, especially the 2D mesh topology, becomes a kind of popular architecture for NoC design, for it is very simple and efficient from a layout perspective [9], [10]. For the traditional routing algorithms, logic-based routing algorithm (e.g.…”
Section: Introductionmentioning
confidence: 99%